Strongly irrsolute precontinuous functions in intuitionistic fuzzy special Topological spaces - TAHA H. AL-DOURY (مجلة جامعة الانبار للعلوم الصرفة, 2009)
: The aim of this paper Is to generalize the concept of intuitionistic fuzzy strongly irresolute precontinuous functions due to B.Krsteska &S. Abbas , [2] to intuitionistic fuzzy special topological spaces. Also we study some of their properties and relations with intuitionistic fuzzy special strongly precontinuous functions .we investigate several characterizing theorem.